Erratum: A cut-off in the TeV gamma-ray spectrum of the SNR Cassiopeia A. Issue 3 (15th February 2018) - Ahnen, MAGIC Collaboration: M L; Ansoldi, S; Antonelli, L A; Arcaro, C; Babić, A; Banerjee, B; Bangale, P; de Almeida, U Barres; Barrio, J A; González, J Becerra; Bednarek, W; Bernardini, E; et al.
Abstract: